Differences in Self-disclosure Levels between Real World and Cyberspace in Students with Introverted Personalities - ALFARIZY, RIZKY; Selian, Sri Nurhayati (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
This research aims to understand the experiences of students with introverted personalities in carrying out self-disclosure (Self-disclosure) in two interaction contexts, namely the real world (face to face) and the virtual world (online). This research uses a qualitative approach with phenomenological methods that focus on subjective meaning of participants' experiences. The research subjects consisted of three Muhammadiyah University of Aceh students who had introverted personality tendencies and actively used social media. Data were obtained through in-depth interviews and non-participant observations, then analyzed using Miles and Huberman's interactive model which includes data reduction, data presentation, and drawing conclusions. Results show that introverted students find it easier to open up in cyberspace due to a sense of security, privacy, anonymity and control over self-expression, whereas in the real world self-openness is limited and selective. Cyberspace provides a safe space for expressing thoughts and feelings, while the real world becomes a means of building more authentic social relationships. The balance of self-openness in both contexts plays an important role in supporting healthy communication and the psychological well-being of introverted students.